(untitled) (Scientific journal of the Fergana State University, 2024)
The study of stylistic means of language is one of the pressing and important issues of linguistics. Each stylistic tool, in combination with the performance of a nominative task in the process of speech, can also be a methodological tool. This article analyzes exaggeration and its types, analyzing them by giving examples from literary works.